A Capability‐Based Framework for Open Innovation: Complementing Absorptive Capacity - Lichtenthaler, Ulrich; Lichtenthaler, Eckhard (Journal of Management Studies, 2009)
abstract We merge research into knowledge management, absorptive capacity, and dynamic capabilities to arrive at an integrative perspective, which considers knowledge exploration, retention, and exploitation inside and outside a firm's boundaries. By complementing the concept of absorptive capacity, we advance towards a capability‐based framework for open innovation processes. We identify the following six ‘knowledge capacities’ as a firm's critical capabilities of managing internal and external knowledge in open innovation processes: inventive, absorptive, transformative, connective, innovative, and desorptive capacity. ‘Knowledge management capacity’ is a dynamic capability, which reconfigures and realigns the knowledge capacities. It refers to a firm's ability to successfully manage its knowledge base over time. The concept may be regarded as a framework for open innovation, as a complement to absorptive capacity, and as a move towards understanding dynamic capabilities for managing knowledge. On this basis, it contributes to explaining interfirm heterogeneity in knowledge and alliance strategies, organizational boundaries, and innovation performance.